The analysis of company policy on the quality of employees in productivity defense during the pandemic - Pamungkas, Ganda Mohamad; Ruspitasari, Widi Dewi; Handoko, Yunus (Management and Entrepreneurship: Trends of Development, 2022)
In improving the quality of employee performance, a conducive working environment is needed so that employees can carry out their responsibilities and obligations properly and professionally so that work culture that lasts and has quality can be created. The company plays a very important role in maintaining the conditions of the employee's work culture so that employees as work resources can be more productive and comfortable with their work and work environment. In line with the demands of a company's target to remain and absorb workers, the productivity defense strategy is the main key to survive so that the economic wheel within the company remains stable even in the pandemic era. The results of the research from the facts in the field show that the provision of policies in the form of motivation and rewards is very important to support the quality of employee performance at the Hero Perdana company. Efforts are made to improve the quality of employee performance.JEL Classification: J08, M54.